From Coping Mechanism to Crisis: The Nexus of Substance Abuse and Mental Health - Kamal Kishore Jamatia (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
The article seeks to understand why individuals turn to substances as coping mechanisms for managing their mental health challenges and examines the progression of substance use from a coping mechanism to a full-blown crisis. The research assesses the adverse effects of prolonged substance abuse on mental health, including the development or exacerbation of mental health disorders. Through a thorough investigation, this study aims to shed light on the factors contributing to the transition from coping to crisis and the subsequent impact on individuals' well-being. Moreover, it identifies effective intervention strategies and support systems that can assist individuals in breaking the cycle of substance abuse, facilitating their recovery, and improving mental health outcomes. By addressing this critical issue, we hope to provide valuable insights that can inform policy, prevention, and treatment efforts in the field of substance abuse and mental health, ultimately promoting healthier and more resilient communities.